Provisional Agenda for the Twenty-Eighth Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper, 2013)
The following is the provisional agenda for the Twenty-Eight Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on October 12, 2013.